2012
DOI: 10.12659/msm.882730
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative pain and satisfaction after dacryocystorhinostomy in patients operated on under local and general anesthesia

Abstract: SummaryBackgroundThere has been only 1 study on postoperative pain after external dacryocystorhinostomy (DCR) that compared pain between 2 groups of patients; 1 group received local anesthesia and the other received general anesthesia. To further characterize the relationship between these 2 types of anesthesia and postoperative pain, we designed a study in which a single patient received these 2 different anesthesia modalities for a short interval on 2 different sides.Material/MethodsThere were 50 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
0
9
0
4
Order By: Relevance
“…Daskaya et al concluded that septoplasty under LAS is more cost-effective than under GA [8]. In a study of 50 patients who had external dacryocystorhinostomy under LA (the use of sedation was not discussed) on one side and under GA on the other, Knezevic et al found that patients were more satisfied with LA than GA and 94% of them would prefer LA during the next procedure [16].…”
Section: Discussionmentioning
confidence: 99%
“…Daskaya et al concluded that septoplasty under LAS is more cost-effective than under GA [8]. In a study of 50 patients who had external dacryocystorhinostomy under LA (the use of sedation was not discussed) on one side and under GA on the other, Knezevic et al found that patients were more satisfied with LA than GA and 94% of them would prefer LA during the next procedure [16].…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] In this study, 72.5% of patients were female and 27.5% male who found similar results in most studies. [ 10 11 ] Gilliland et al ., believed the predilection in females may be due to the smaller nasolacrimal canal diameter in females than in men and hormonal factors. [ 12 ] About 47.5% of patients in this study were in the age group above 50 years, which is in harmony with Yoon et al ., study[ 13 ] and 44.8% of female cases were in menopause stage, this finding confirms the prevalence of this disorder in women in the menopause stage.…”
Section: Discussionmentioning
confidence: 99%
“…This study included 55.2% females and 44.7% males, which is similar to study conducted by M. Alnawaiseh et al 2 (Gender [Female:Male] 97 (66.4%) : 49 (33.6%)) and most other studies. 10,11 The smaller nasolacrimal canal diameter and hormonal factors may be responsible for the increased predilection in females. Majority of the patients were above 50 years of age.…”
Section: Discussionmentioning
confidence: 99%